A study to assess the microbial profile and index of microbial air contamination in dental operatories - Geetha Banu Shanmugaraj; Arthi Krishna Rao (Wolters Kluwer Medknow Publications, 2020)
Background: Microbial contamination of air in dental operatory is an important source of infection. In this study, passive air sampling using settle plates was used as an effective method to assess the microbial profile and index of microbial air contamination (IMA) in dental operatories. Aim: To assess the microbial profile and index of microbial air contamination (IMA) in dental operatories. Setting and Design: This study design was a experimental cum diagnosis study and was conducted in four outpatient dental operatories in a self-financing dental college using stratified random sampling technique. Materials and Methods: Twenty air samples were collected by leaving blood agar plates open for 1 h, 1 m above the floor and 1 m from the wall. After incubation at 37°C for 48 h, colonies were counted to assess the number of colony-forming units (CFUs) per plate. The number of CFU is the IMA. The evaluation of aerobic bacterial and fungal profiles of representative colonies was done by standard microbiological methods. Results: Independent sample 't' test was applied for this study. All air samples collected near the dental treatment unit showed more contamination than the ambient air. As per the IMA classes, the IMA near the dental treatment unit ranged from fair to poor. IMA of ambient air in all the four operatories was within the acceptable values. The most common microorganism isolated was Staphylococcus species. Conclusion: Passive air sampling is one of the effective ways of quantifying airborne bacteria as used in the present study. Air microbial level evaluation is a step towards cross-infection prevention.